2018
DOI: 10.1111/ijd.14213
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin gene polymorphisms in Iranian ichthyosis vulgaris and atopic dermatitis patients

Abstract: Background Filaggrin is a key structural epidermal protein in terminal differentiation and formation of skin barrier. The important role of filaggrin and its effects in various cutaneous and noncutaneous disorders initiated a cascade of considerable research in recent years. Loss‐of‐function mutations in FLG, the human gene encoding profilaggrin/filaggrin, is the cause of the common skin condition ichthyosis vulgaris (IV) and major genetic predisposing factor for atopic dermatitis (AD). Several null mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Although their prevalence of the two most common filaggrin ( FLG ) mutations leading to AD (R501X and 2282del4) is lower, patients of African descent appear to be at greater risk for severe AD [16, 17]. Other studies have reported the prevalence of different FLG mutations in Asian patients (S1695X, Q1701X, Q1745X, Y1767X, Q1790X, S2554X, S2889X, S3296X, 3222del4, S1515X, Q2417X, and K4022X) and Middle Eastern patients (S417S and D1921N, among others) [24, 25]. Pruritus may be more severe in patients with darker skin [17, 19, 26, 27].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although their prevalence of the two most common filaggrin ( FLG ) mutations leading to AD (R501X and 2282del4) is lower, patients of African descent appear to be at greater risk for severe AD [16, 17]. Other studies have reported the prevalence of different FLG mutations in Asian patients (S1695X, Q1701X, Q1745X, Y1767X, Q1790X, S2554X, S2889X, S3296X, 3222del4, S1515X, Q2417X, and K4022X) and Middle Eastern patients (S417S and D1921N, among others) [24, 25]. Pruritus may be more severe in patients with darker skin [17, 19, 26, 27].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…For example, it has been demonstrated that greater helper T cell Th17/Th22 polarization is observed in Asian populations with a combined manifest of AD and psoriasis [ 7 , 8 ]. Loss-of-function mutation in the filaggrin ( FLG ) gene is another well-recognized risk factor leading to severe AD with a diverge reported prevalence in different ethnic groups [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. On top of the regular risk factors, a growing number of studies about the association between intestinal microbiome dysbiosis and AD has emerged owing to the recent advancement in next-generation sequencing (NGS) [ 13 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was a reanalysis of our previous investigations performed on FLG polymorphisms in AD published in 2018. 11 In the stated study we identified 45 FLG variants. Here, we selected the most frequent FLG variants to investigate their association with clinical and laboratory manifestations of AD in Iranian young patients.…”
Section: Methodsmentioning
confidence: 99%
“…Association between FLG polymorphisms and the early onset of AD disease.In 2018, a novel polymorphism was reported in Iranian AD patients by Hasani et al(11), with codon change of tcT>tcC and aa change of p.S417S. In 2018, a novel polymorphism was reported in Iranian AD patients by Hasani et al(11), with codon change of Gac>Aac and aa change of p.H1961Q.…”
mentioning
confidence: 99%